(untitled) (Revista Justiça do Direito, 2019)
One of the most well-articulated rules of international human rights law, the right to participate in politics and public life through the suffrage, is also one of the more frequently denied for individuals with disabilities. This work intents to draw a parallel, based on the United Nations Convention on the Rights of Persons with Disabilities, about the structural power that the right to vote and to be voted can offer to all individuals who, somehow, are daily prevented from exercising them. The article 29 of this Convention, addresses the design and implementation of an electoral process that is non-discriminatory, while also requiring states to provide voters with disability-related other facilitative measures to enable their equal rights. Sovereignty makes the rights rise in each and every citizen and allows them to participate in political decision-making and to be part of the primary element in shaping the public interest. During the research, we look more closely at the rights of minorities, emphasizing the ones connected with persons with disabilities in the decision-making process, especially the political ones, so that their rights can be heard and enforced. Throughout the study, we observed that the guarantee of the right to suffrage and its manifestations requires, previously, the elimination of architectural, social, economic and attitudinal obstacles, among others. The rules contained in the Brazilian Inclusion Law and the UN Convention on the Rights of Persons with Disabilities are intended to shape parameters to protect and enforce this right of citizens with disabilities and drive the expression of this minority in all its political potential. Emerging practices around the globe, as in Spain and Germany, corroborating that persons with disabilities can be successfully incorporated in all phases of an electoral process. The suffrage rights become, therefore, a channel for participation and transformation of the subservient individual to a citizen capable of influencing decisions that will be taken on his behalf.